AlGaAs/Si dual‐junction tandem solar cells by epitaxial lift‐off and print‐transfer‐assisted direct bonding. Issue 1 (4th January 2018) - Xiong, Kanglin; Mi, Hongyi; Chang, Tzu‐Hsuan; Liu, Dong; Xia, Zhenyang; Wu, Meng‐Yin; Yin, Xin; Gong, Shaoqin; Zhou, Weidong; Shin, Jae Cheol; Li, Xiuling; Arnold, Michael; et al.
Abstract: A novel method is developed to realize a III‐V/Si dual‐junction photovoltaic cell by combining epitaxial lift‐off (ELO) and print‐transfer‐assisted bonding methods. The adoption of ELO enables III‐V wafers to be recycled and reused, which can further lower the cost of III‐V/Si photovoltaic panels. For demonstration, high crystal quality, micrometer‐thick, GaAs/AlGaAs/GaAs films are lifted off, transferred, and directly bonded onto Si wafer without the use of any adhesive or bonding agents. The bonding interface is optically transparent and conductive both thermally and electrically. Prototype AlGaAs/Si dual‐junction tandem solar cells have been fabricated and exhibit decent performance. Abstract : A novel method is developed to realize an III‐V/Si multijunction photovoltaic device by combining the epitaxial lift‐off (ELO) and print‐transfer‐assisted bonding methods. The adoption of ELO enables III‐V wafers to be recycled and reused, which is promising to further lower the cost of III‐V/Si photovoltaic panels.